Nonclassical Properties and Generation of Superposition State of Excited Coherent States of Motion of Trapped Ion (Journal of Atomic and Molecular Sciences, 2011)
We have studied the intensity squeezing of superposition state of excited coherent states and proposed a new method to prepare superposition state of excited coherent states of vibrational motion of trapped ion. This method is based on the interaction of a single trapped ion with two traveling wave light fields with different frequencies. An obvious merit of this method is that it works without application of the perturbation theory.
Keywords: trapped ion; excited coherent states; intensity squeezing.